Small Ruminants for Diverse Products and Profits - Babu, R. Narendra; Sivakumar, P. (Indian Farming, 2015)
Production of meat products with adequate process and quality control will facilitate our products to enter into global markets and fetch higher returns. The future success of meat industry in India depends on converting scientific knowledge into value added systems by improving linkages, infrastructure, adjusting taxation and food laws as well as drawing clear plans which benefits producer, processor and consumers.